Effectiveness of guessing meaning from context in improving students' word-attack skills at University of Labor and Social Affairs - Đàm, Lan Hương (ĐHNN, 2017)
Chapter 1, Introduction, presents the background and statement of the problem, the purpose, and the design as well as the scope of thestudy. Chapter 2, Literature Review, discusses issues of reading, reading processes, major approaches to teaching reading, reading strategies in general and the strategy of guessing meaning from context in particular. Chapter 3, Research Design and Methods, explains the methodology used in the study including the population information, instrumentation, and data collection and data analysis. Chapter 4, Findings and Discussion, reports the findings as well the discussion of the results. Chapter 5, Conclusion,offers a summary of the findings and further implication forusing the strategy of guessing from context in teaching reading skills.